PROFESSIONAL EXAMINATIONS: ACCOUNTING PRACTICE. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1961)
This article presents accounting problems which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants and were presented as the second half of the C.P.A. examination in accounting practice on November 3, 1960. One of the questions asks to prepare a statement showing how cash will be distributed among partners by installments as it becomes available. In yet another question it asks to prepare a worksheet showing account balances per books, any adjustments one can consider necessary, and adjusted balances. Also, indicate which balance one would consider to be current, which balances noncurrent, and which balances would be shown in the stockholders' equity section of the balance sheet. The question further asks to prepare schedules of inventories, depreciation, and deferred taxes in good form. The Johnson Appliance Co. started business on January 1, 1950. Separate accounts were established for installment and cash sales, but no perpetual inventory record was maintained.